Cervical Cannulation for Surgical Repair of Congenital Cardiac Defects in Infants and Small Children - Pankaj Garg; Arvind Kumar Bishnoi; Ketav Lakhia; Parth Solanki; Jigar Surti; Komal Shah; Sanjay Patel (Brazilian Journal of Cardiovascular Surgery)
Abstract INTRODUCTION: The biggest challenge faced in minimally invasive pediatric cardiac surgery is cannulation for cardiopulmonary bypass. Our technique and experience of cervical cannulation in infants and small children for repair of congenital cardiac defects is reported in this study. METHODS: From January 2013 to June 2015, 37 children (22 males) with mean age of 17.97±8.63 months and weight of 8.06±1.59 kg were operated on for congenital cardiac defects through right lateral thoracotomy. The most common diagnosis was ventricular septal defect (18 patients). In all patients, right common carotid artery, right internal jugular vein and inferior vena cava were cannulated for institution of cardiopulmonary bypass and aorta was cross clamped through right 2nd intercostal space. RESULTS: There were no deaths or any major complications related to cervical cannulation. Common carotid artery cannulation provided adequate arterial inflow while internal jugular vein with inferior vena cava provided adequate venous return in all patients. No patient required conversion to sternotomy or developed vascular, neurological or wound related complications. Three patients had residual lesions (small leak across ventricular septal defect patch-2, Grade II left atrio-ventricular valve regurgitation-1) and one patient had mild left ventricular dysfunction. At discharge, both common carotid artery and internal jugular vein were patent on color Doppler ultrasonography in all patients. In a mean follow-up period of 11.4±2.85 months, all patients were doing well. No patient had any wound related, neurological or vascular complication. No patient had residual leak across ventricular septal defect patch. CONCLUSION: Cervical cannulation of common carotid artery and internal jugular vein is a safe, reliable, efficient and quick method for institution of cardiopulmonary bypass in minimally invasive pediatric cardiac surgery.